2000
DOI: 10.1046/j.1365-2125.2000.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of adherence to lipid‐lowering drug treatment. A comparison of utilization patterns in defined populations in Funen, Denmark and Bologna, Italy

Abstract: Aims The objective was to explore differences in lipid‐lowering drug (LLD) prescribing in Italy and Denmark. Methods We used two geographical areas with computerized drug prescription records in defined populations, one in Funen, Denmark with 500 000 inhabitants, the other in Bologna, Italy with 400 000 inhabitants. Prescriptions for patients who had purchased a LLD from 1994 until 1996 were retrieved as well as coprescriptions of antidiabetic and cardiovascular drugs as markers for diabetes and cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 13 publications
6
37
0
Order By: Relevance
“…However, PDD would be closer to actual use than assuming a medicine use of one DDD per day, as some DDDs are doses rarely prescribed and medicines are often used for various indications [16]. As suggested elsewhere, for statins, a more relevant measure of daily dose for some therapeutic regimes might be one tablet, as tablets come in different strengths [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, PDD would be closer to actual use than assuming a medicine use of one DDD per day, as some DDDs are doses rarely prescribed and medicines are often used for various indications [16]. As suggested elsewhere, for statins, a more relevant measure of daily dose for some therapeutic regimes might be one tablet, as tablets come in different strengths [29].…”
Section: Discussionmentioning
confidence: 99%
“…We must consider other explanations, and these may lie in factors unique to each country: for example, differences between Norway and Denmark may reflect the involvement of Norwegian doctors in seminal trials, while in Denmark these drugs were only reimbursed from 1998 onwards and their use has lagged behind other countries. Low use in Italy may reflect low coronary morbidity or poor adherence of Italian patients to statins, worse than elsewhere in Europe 4. Other differences may lie in national guidance and policies.…”
Section: Commentmentioning
confidence: 99%
“…In 1996, Danish cardiologists estimated that the prevalence of patients who needed LLDs was 5% of the total population (6). We found that in the year following the issue of guidelines, about 1% of all individuals B65 years and 4% of all individuals ]65 years were treated with LLDs.…”
Section: Discussionmentioning
confidence: 83%
“…However, studies from a number of different European countries show that patients with an increased risk of CHD are not offered optimal prevention (5). Particularly, a substantial under-use of lipid-lowering drugs (LLDs) has come to attention (5,6).…”
Section: Methodsmentioning
confidence: 99%